State of information technology adoption by internal audit department in Malaysian public sector - Ahmi, Aidi; Saidin, Siti Zabedah; Abdullah, Akilah; Che Ahmad, Ayoib; Ismail, Noor Azizi (EconJournals, 2016)
The objective of this paper is to discuss the level of information technology (IT) adoption by internal audit unit (IAU) in Malaysian public sector, the types of the IT applications implemented and the purposes of its implementation.In recent years, internal auditors have begun to realize the important of IT to perform their audit tasks. Specifically, the use of Computer Assisted Auditing Tools and Techniques (CAATTs) can help in terms of audit efficiency and effectiveness.This research employed an online and mail survey methods to gather data from 266 head of internal auditors in Malaysian public sector. The results show that the level of IT adoption by IAU in Malaysian public sector is high.However, with regards to the usage of IT specifically in auditing, it is considerably low despite the huge benefits that have been offered by the technology. Due to the nature of the data collection method, the study might reflects the perfection of the respondents which may not translate into actual practice.Further research should consider a field study to examine the real issue regarding the IT implementation in public sector.